E-Commerce Trend: Analysis of Student Online Shopping Activities - Majid, Basrul Abdul; Sofyan, Zuhra (Journal of Economics Education and Entrepreneurship, 2023)
This study aims to analyze the specialization of online shopping for college students using descriptive analysis techniques. The sample used is 195 respondents using the total sampling technique. The student learned many things about economics and business. With e-commerce, this should be an opportunity to apply what has been learned in practice. These students can start by opening an online business. But they prefer to use e-commerce to buy specific items rather than sell products. The results showed that the categorization of student specialization (1) based on the device used to access e-commerce applications was a smartphone (android) as much as 84.10%; (2) by product category is fashion 45.64%; (3) the intensity of shopping frequency not less than three times a month is 51.79%; (4) based on the monthly budget in online shopping is less than one hundred thousand rupiahs is as much as 56.92%; (5) frequently used application is Shopee 72.31%, and (6) payment transaction system using Cash on Delivery (COD) as much as 72.31%.